2011
DOI: 10.1634/theoncologist.2010-0256
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 18F-Fluorodeoxyglucose Positron Emission Tomography in Thyroid Neoplasms

Abstract: After completing this course, the reader will be able to:1. Evaluate and apply evidence regarding the use of FDG-PET scans in patients with thyroid nodules.2. Identify differentiated thyroid carcinoma (DTC) patients who could benefit from FDG-PET scanning.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…x Nuclear-medicine studies show that 18 F-FDG-positive-DTC patients have a worse prognosis [36,37]. In our study, only 63 RR patients underwent 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 64%
“…x Nuclear-medicine studies show that 18 F-FDG-positive-DTC patients have a worse prognosis [36,37]. In our study, only 63 RR patients underwent 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 64%
“…The reasons why RAI avidity might have been a significant prognostic factor are 2-fold. First, non-RAI-avid DM is generally less differentiated and so behaves more aggressively 1921. Second, non-RAI-avid DM are less responsive to RAI therapy 21.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases are usually diagnosed by pre-operative USG of the regional neck lymph nodes. [30,31] Jeong et al compared the diagnostic accuracy of 18 F-FDG PET/CT to that of USG for the pre-operative evaluation of CLN status in patients with papillary thyroid cancer. The study concluded that FDG-PET/CT did not provide additional benefits over USG for lateral neck lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%